Juvenile thyroid malignancy - Parelkar, Sandesh; Joshi, Milind (Indian Journal of Medical and Paediatric Oncology, 2009)
Thyroid malignancy is an uncommon tumor of the pediatric population. Patients can present with asymptomatic thyroid nodule and it requires thorough work up to rule out the malignancy. Radiological and pathological procedures are a standard part of the management. A 10-year-old girl had asymptomatic thyroid nodule; the cytological examination and the frozen section and final histology of the nodule was different each time. The girl had to undergo total thyroidectomy on the basis of histology of the nodule which was well differentiated papillary carcinoma of thyroid and is under regular follow-up for last two years on thyroid supplementation.
Keywords: Juvenile thyroid malignancy; papillary carcinoma; thyroid nodule